Exploring The Clinical Pharmacokinetics of Eplerenone: A Systematic Review of Published Studies. - Kanan, Mohammed; Alshahrani, Rahaf; Alqahtani, Amal; Wazi, Nada; Alsaqiti, Khawlah; Alassaf, Sana; Alhomaidi, Miad; Abdulrahman, Samar; Jibril, Reem; Alanazi, Haya; Alothman, Jory; Al Obaid, Shahad; et al. (Pharmacy Practice (1886-3655))
Eplerenone is the first selective aldosterone antagonist to manage hypertension and congestive heart failure. This comprehensive review aims to collate all the published pharmacokinetic (PK) data on eplerenone by scavenging the relevant articles following oral route of administration in human subjects (healthy & diseased). Five databases, Science Direct, Cochrane Library, EBSCO, Google Scholar, and PubMed, were used systematically to retrieve the relevant studies containing at least one reported PK parameter of eplerenone. A total of 983 articles were identified, in which 08 studies were included after applying the inclusion/exclusion criteria. Eplerenone shows the linear PK profile as the area under the plasma concentration-time curve (AUC) and maximum plasma concentration (Cmax) increase dose-dependently. The Cmax was found to be increased by 2-fold following the administration of multiple doses in healthy as well as in subjects with renal impairment in comparison with single dose. In dialysis subjects, the peak time (Tmax) was significantly shorter than that of the healthy population, 1.28 ± 0.47 hr vs. 2.22 ± 0.75 hr. A significant increase in oral clearance (CL/F) was observed in dialysis patients compared to normal subjects after giving multiple doses. Moreover, co-administration of ketoconazole with eplerenone showed a 1.7-fold increase in Cmax. The current systematic review summarizes all the available PK parameters of eplerenone from the possible accessible studies that can assist clinicians in dosage adjustments in patients with renal failure and avoiding drug-drug interactions.